Validation of a reverse-phase high-performance liquid chromatography method for the determination of amino acids in gelatins by application of 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate reagent - Mohd Ismail, Azilawati; Mat Hashim, Dzulkifly; Bakar, Jamilah; Ismail, Amin (Elsevier, 2014)
In-house method validation was conducted to determine amino acid composition in gelatin by a pre-column derivatization procedure with the 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate reagent. The analytical parameters revealed that the validated method was capable of selectively performing a good chromatographic separation for 18 amino acids in less than 40 min; the overall detection and quantitation limit for amino acids fell into ranges of 5.68–12.48 and 36.0–39.0 pmol/μl, respectively; the matrix effect was not observed, and the linearity range was 37.5–1000 pmol/μl. The accuracy (precision and recovery) analyses of the method were conducted under repeatable conditions on different days in random order. Method precision revealed by HorRat values was significantly less than 2, except for histidine with a precision of 2.19, and the method recoveries had a range of 80–115% except for alanine which was recovered at 79.4%. The findings were reproducible and accurately defined, and the method was found to be suited to routine analysis of amino acid composition in gelatin-based ingredients.